ANALISIS DAN PERANCANGAN WEBSITE SMA TRIMURTI MENGGUNAKAN METODE WEBQUAL - Muhammad aswin albian; januar wibowo; Endra Rahmawati (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2018)
The growing of ICT brought websites as an integral part of organization/company in terms of customer services. It is necessary to measure the website quality to identify end-user satisfaction and obtain the feedback. In this study, the website quality of Trimurti Surabaya highschool is measured using WebQual method. WebQual is an instrument for assessing the quality of websites from the perspective of the customer as the end user. Multiple linear regression is used to examine the association of each dimension of WebQual with user satisfaction. It is concluded that one of WebQual’ dimensions, i.e. interaction quality, does not influence user satisfaction significantly.